2017
DOI: 10.4172/2090-7214.1000257
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Birth Preparedness and Complication Readiness among Pregnant Mothers Attending Ante Natal Care Service in Mizan-Tepi University Teaching Hospital, South West Ethiopia

Abstract: Background: Every pregnancy is risk of having life-threatening obstetric complications. A birth preparedness package promotes active preparation and assists in decision-making for healthcare seeking in case of such complication. Although its importance is fact, it is low in Ethiopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…A similar study in Tamale Teaching Hospital in the Northern Region of Ghana found BP/CR levels of 43.7%, while a mixed health facility and community-based study among teenage mothers in the Ledzorkuku Krowor Municipal Assembly in the Greater Accra Region reported 40.0% to be more birthprepared [16,23]. Equally low rates have been reported in other countries with 20% BP/ CR in a health facility-based study in Tharaka Nithi County in Kenya, 41.1% in Mizan-Tepi University Hospital in Southwest Ethiopia and 47.8% in a slumbased study with a functional maternal and child health program in Indore in India [24][25][26]. Discrepancies between our findings and these studies could be explained by socioeconomic factors.…”
Section: Levels Of Bp/cr Among Women Who Recently Deliveredmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study in Tamale Teaching Hospital in the Northern Region of Ghana found BP/CR levels of 43.7%, while a mixed health facility and community-based study among teenage mothers in the Ledzorkuku Krowor Municipal Assembly in the Greater Accra Region reported 40.0% to be more birthprepared [16,23]. Equally low rates have been reported in other countries with 20% BP/ CR in a health facility-based study in Tharaka Nithi County in Kenya, 41.1% in Mizan-Tepi University Hospital in Southwest Ethiopia and 47.8% in a slumbased study with a functional maternal and child health program in Indore in India [24][25][26]. Discrepancies between our findings and these studies could be explained by socioeconomic factors.…”
Section: Levels Of Bp/cr Among Women Who Recently Deliveredmentioning
confidence: 99%
“…Employed women are generally known to have more autonomy to make decisions concerning their health, thereby preventing delays in seeking healthcare [36][37][38]. In contrast, studies in South West Ethiopia and northern Ghana found no association between occupation and BP/CR [15,39] . This could be attributed to the fact that most women in the Kassena Nankana District of Ghana were housewives and the Ethiopian government's free provision of ambulance and other maternal and child health services [15,39].…”
Section: Predictors Of Bp/crmentioning
confidence: 99%
“…The major causes of maternal deaths are obstructed/prolonged labour (13%), ruptured uterus (12%), severe preeclampsia/ eclampsia (11%) and malaria (9%). Moreover, 6% of all maternal deaths were attributable to complications from abortion [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…The sample size was determined by using a formula for the estimation of a single population proportion. The magnitude of BPCR practice was 41.1% (p=0.411) [6]. Sample size computed using a 95% confidence interval, 5% margin of error (d), and 15% of the sample size was added for nonresponse.…”
Section: Sample Size and Sampling Proceduresmentioning
confidence: 99%
“…In Ethiopia, the majority of pregnant women and families do not know how to recognize the dangerous signs of complications. This was exposed families to waste a great deal of time in recognizing the problem, getting organized, getting money, finding transport, and reaching to an appropriate referral facility after a complication occurs [6].…”
Section: Introductionmentioning
confidence: 99%